Profesionalisme Guru Di Era Teknologi Disrupsi - Adi Priyono; Ardian Arief (Jurnal Ilmiah Profesi Guru (JIPG), 2022)
The quality of human resources in a country cannot be separated from the role of an educator, especially a teacher. Teachers who play an important role in various efforts to improve the quality of good and professional human resources. The competence of a professional teacher is one of the most important elements that an educator must have. If a teacher does not have a professional attitude then students will find it difficult to develop as the role of the teacher in the era of disruptive technology is a teacher who is aware of rapidly developing technological advances, without implementing the cultivation of good character for students. The era of disruptive technology is a big and tough challenge for Indonesian teachers. Because in reality our teachers face the era of disrupted technology when they are still preoccupied with the burden of delivering knowledge content plus various administrative tasks as teachers. Various ways must be done by various parties in the education unit in responding to the era of disrupted technology. The government has also implemented a program to improve the quality of education and teacher professionalism by holding a certification program, PKG (Pusat Kegiatan Guru), MGMP (Musyawarah Guru Mata Pelajaran), KKG (Kelompok Kerja Guru), improving welfare by seeking teacher professional allowances etc. to improve the professionalism of a teacher in the face of the era of disruptive technology. Therefore, this research is using a qualitative descriptive approach. Data collection was done by interview, observation, and literature study.